Dominican Republic : 2017 Article IV Consultation- Press Release; Staff Report; and Statement by the Executive Director for the Dominican Republic. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights the Dominican economy's strong growth momentum over the past three years, which is now beginning to taper off toward potential. Growth has averaged 7 percent since 2014, outperforming most emerging market economies and all economies in the Americas, buoyed by domestic demand. Real GDP expanded by 6.6 percent in 2016. The economic outlook is favorable. Growth is expected to slow toward the potential rate of about 5 percent from 2017 onward, while the recent rise in fuel prices will push inflation to target and will widen the current account deficit moderately from 2017 onward. Risks around this baseline outlook are balanced.